Avaliação da composição química, atividade antioxidante, antibacteriana, antinoceptiva, antiinflamatória e toxicidade do extrato metanólico e frações de folhas de Spondias sp. (Anacardiaceae) - Silva, Gabriel Araújo da (2012)
Spondias sp. (Anacardiaceae), popularly known as cajá-umbu, is an endemic plant from Northeastern Brazil, where their leaves are widely used in folk medicine to treat inflammatory processes, while their fruits have a great agro industrial potential. This study was designed to evaluate hepatoprotective, antinociceptive, antioxidant, antimicrobial and anti-inflammatory properties, as well as the acute toxicity and repeated dose 28, using a methanolic extract (MES), a fraction rich in flavonoids (FRF) and a precipitate from Spondias sp.leaves. The antioxidant activity of them was valued to evaluate their free radical scavenger capacity by DPPH test, whereas MES and FRF were used to evaluate while the preventive action on carbon tetrachloride (CCl4)-induced hepatotoxicity. Seven groups (n=5) of female Wistar rats were used as follows: control group, CCl4-intoxicated group treated with EMS (500 mg/kg) for 7 days, three CCl4-intoxicated groups treated with FRF (25, 50 and 75 mg/kg) for 7 days and the CCl4-intoxicated group treated with Legalon ® (silimarina; (phytotherapeutic reference) (50 mg/kg; 7 days). MES and FRF showed a protective action against liver injury induced by CCl4, being observed a significant reduction of serum enzyme activity marker of liver damage (alanine transaminase and aspartate transaminase). On the other hand, the lipid peroxidation (SRAT) decrease, as well as the increase of glutathione content and enzyme activity of antioxidant defense system (SOD, CAT, GPx) toward near normal values indicated the ability of EMS to restore the oxidative imbalance induced by CCl4. The histological analysis confirmed the hepatoprotection, compared to degenerative changes in CCl4-treated group. This hepatoprotetor effect was similar to that shown by Legalon®. The in vitro high antioxidant capacity of extract (93.16 ± 1.00%) showed analogous results to those obtained by Carduus marianus BHT (reference standard). This fact explains the obtained results in vivo. Although no antimicrobial activity was detected, EMS and FRF promoted the antinociceptive effect induced in the second phase by the intraplantar formalin test, evidencing the anti-inflammatory action; confirmed by the carrageenan-induced peritonitis model. The evaluation of the mechanical allodynia (CFA a 80%) demonstrated the involvement of the Spondias sp. chemical composition in the anti-inflammatory activity toward the acute processes. The acute exposure and repeated dose during 28 days did not produce significant changes in the parameters that evaluate toxicity. Together the experimental results reveal, that Spondias sp. leaf extracts have a promising potential in pharmaceutical area, and due to its non-toxic condition present efficiency and security